Primary Students’ Perception towards Cultural Differences in The School Environment - Yeny Prastiwi (Jurnal VARIDIKA, 2020)
This article aims at uncovering how the elementary students’ responses to cultural differences. The students as the object of the present research is from four different Islamic schools. In this sense, the students are getting used socialize with homogeneous culture. This research was conducted through participatory action research where the member of the research she is a foreigner – Japanese and student of BIPA (Indonesian Language for foreign speaker) program – introduces her culture to six grade students (eleven to twelve years old children). The research data was collected through questionnaires. The result of the study indicated by the collected questionnaire shows that most of the students: fifty-eight form seventy-seven students like to the introduction of foreign culture, particularly conducted by foreign people. They are happy with the foreign people in their school introducing in Japanese culture, such as short lyrics Japanese song. Students’ active participation in class activity perceived as their acceptation or positive manner to foreign culture in their school environment.